Role of antioxidant vitamins and trace elements in mastitis in dairy cows - Yang, Feng Li; Li, Xiao Shan (Journal of Advanced Veterinary and Animal Research, 2014)
Mastitis is associated with release of free radicals, increased total oxidant capacity and decreased total antioxidants capacity in milk. Antioxidant vitamins and minerals protect the body from free radicals either by directly scavenging free radicals or by inhibiting the activity of oxidizing enzymes. The supplementation of mastitic dairy cows with antioxidant vitamins as vitamin A (VA) and ?carotene (BC), vitamin C (VC), vitamin E (VE), and antioxidant minerals as selenium (Se), Zinc (Zn) and copper (Cu) is very important to help the animal recover early. The aim of this review was to discuss the oxidative stress in dairy cows mastitis, and the roles of VA and BC, VC, VE, Se, Zn, and Cu in mastitis of dairy cows. Before deciding to supplement dairy cow rations with the levels of vitamins and minerals, dairy farmers should have their animal feeds tested and their rations evaluated by a competent dairy cow nutritionist and a trustworthy laboratory to be sure what levels of supplementation may be warranted. While inadequate intake and absorption of certain nutrients may result in a weakened immune system and perhaps more mastitis during the lactation period, unjustified supplementation can be expensive and lead to other animal health problems. http://dx.doi.org/10.5455/javar.2015.b48